Propaganda by Deed and the Destruction of Authority in Ahlam Alnisa' Alharem: An Goldman's Anarcho-Feminist Reading - Rendi Muhammad Fauzi; Rohanda Rohanda; Khomisah Khomisah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This study examines the forms of women's resistance against patriarchal structures in Fatima Mernissi's novel, Ahlam Alnisa' Alharem. In contrast to previous liberal feminist approaches that generally emphasize negotiation and systemic reform, this research employs Emma Goldman's Anarcho-Feminist perspective to analyze direct and confrontational resistance strategies. Utilizing a descriptive-analytical qualitative method, the present study draws upon two primary concepts: Propaganda by Deed and The Destruction of Authority. The findings indicate that the female characters within the Harem articulate their autonomy through direct action, the assertion of bodily rights, and civil disobedience, rather than mere compliance. Furthermore, these acts aim to deconstruct three intersecting forms of authority conceptually referred to as the "trinity of oppression," which encompasses the manipulation of religious tradition, state repression represented by territorial boundaries (hudud), and social class hierarchies. The culmination of this resistance is the liberation of women from internalized patriarchal control, identified within the narrative as the "internal tyrant". In conclusion, emancipation within this text is realized through the dismantling of both structural confinement (the physical spaces of the Harem) and psychological subjugation.